Evidence-based prevention and management of febrile neutropenia in patients undergoing chemotherapy for breast cancer (基于循证的乳腺癌化疗患者粒细胞减少性发热的预防与管理) - BIAN Guanyue (边关月); CHEN Qian (陈茜); SUN Ling (孙玲) (Association of Integrative Nursing, 2021)
Objective To apply the existing best evidence of the prevention and management of febrile neutropenia after chemotherapy to nursing practice in order to reduce the incidence of complications in patients with breast cancer. Methods Using the JBI clinical evidence practice application system, based on the existing best evidence, six review criteria were developed and applied to nursing practice. The quality review and process improvement were carried out in one ward for 6 months. In the baseline review process, 349 times of chemotherapy in 128 cases were statistically reviewed. In the second-round review process, 349 times of chemotherapy in 128 cases were statistically reviewed. Fifty patients were followed up and their self-efficacy was evaluated by using General Efficacy Scale (GES). Results After the second round of examination, all the examination standards reached 100. 00% except the seventh article(patients had to follow the doctor's advice to complete medical examination and recoding) , which rose to 88. 2%. According to the follow-up outcomes, patients had achieved higher GES scores after implementation of evidence-based prevention and management. Conclusion The evidence-based quality review program has significantly improved nursing practice in the prevention and management of febrile neutropenia in breast cancer patients undergoing chemotherapy, but it still needs to be reviewed and improved to improve the quality of nursing. (目的 将现有的化疗后粒细胞减少性发热的预防与治疗的最佳证据应用到护理实践中, 以减少化疗患者并发症的发生。方法 采用JBI临床证据实践应用系统, 基于现有的最佳证据, 制定9条审查标准, 应用于护理实践, 在1个病区开展6个月的质量审查和流程改进。基线审查中, 选取128名乳腺癌化疗患者, 对其中的349次化疗进行统计审查; 第2轮审查中, 选取128名乳腺癌化疗患者, 对其中的349次化疗进行统计审查。另外, 随访50名患者, 分别在改善前和改善后采用一般自我效能量表(GES)评估患者自我效能。结果 经过第 2轮审查, 除第7条(患者均遵医完善检查和记录)上升至88. 2%, 其余审查标准均达到100. 00%。随访结果显示, 改善后患者GES量表评分较改善前得到有效提升(P＜0. 05)。结论 基于循证的质量审查项目改善了乳腺癌化疗患者粒细胞减少性发热的预防与管理的护理实践, 但仍需不断审查改进, 以提高护理质量。)